Retinoic acid receptor signaling levels and antigen dose regulate gut homing receptor expression on CD8(+) T cells - Svensson, M (Mucosal Immunol, 2008)
Recent studies have highlighted a central role for intestinal dendritic cells (DCs) and vitamin A metabolite retinoic acid (RA) in the generation of α4β7(+) CCR9(+) “gut tropic” effector T cells. Here, using RA-responsive element reporter mice, we demonstrate that both splenic and mesenteric lymph node (MLN) DCs enhanced retinoic acid receptor (RAR) signaling in CD8(+) T cells; however, only a subset of MLN DCs, expressing the integrin α-chain CD103, induced an early RAR signal that is required for efficient CCR9 induction. MLN-primed CD8(+) T cells also received enhanced RAR-dependent signals compared with splenic-primed CD8(+) T cells in vivo. Further DC-mediated induction of gut homing receptors was inhibited at a high antigen dose without influencing RAR signaling events, and resulted in less efficient CD8(+) T-cell entry into the small intestinal mucosa. These results highlight a complex interplay between antigen dose and DC subset-induced RAR signaling events in the generation of tissue tropic effector T-cell subsets.